A new species of the enigmatic genus Osphyoplesius from Sicily (Coleoptera: Tenebrionoidea: Pythidae) - Magrini, Paolo; Uliana, Marco (Zootaxa, 2015)
Osphyoplesius is an obscure Palearctic genus tentatively placed in Pythidae, comprising one species from Crimea and one from Greece, each of them collected only once. A third species is here described from Sicily, based on recently collected specimens. Despite the poor sample, statistic analysis of morphometrical data allowed to confirm the differentiation between the new species and its closest relative, and revealed the existence of sexual dimorphism in the genus.